PENGARUH PENGAWASAN DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA PEGAWAI APARATUR SIPIL NEGARA PADA DINAS KETAHANAN PANGAN KOTA BIMA - Kusumayadi, Firmansyah (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This research aims to determine the significant influence of supervision and work environment on the work spirit of State Civil Servants at the Bima City Food Security Service. This type of research is associative using quantitative data. The population and sample in this study were 30 State Civil Service employees using a total sampling technique. Data collection techniques include observation, interviews, questionnaires, documentation. Data analysis techniques use validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, coefficient of determination, t tests and f tests with the help of SPSS version 23 for Windows. The results of the research show that there is a positive and significant influence of supervision and the work environment on the work spirit of State Civil Service employees at the Bima City Food Security Service.